Aplikasi Theory of Planned Behavior dalam Membangkitkan Niat Pasien untuk Melakukan Operasi Katarak - Dian Anggraini Wikamorys; Thinni Nurul Rochmach (Universitas Airlangga, 2017)
Surgery is the follow-up actions of diagnosis. The biggest revenue in Clinics comes from surgery.The number of patients suffering cataract who do not undergo cataract surgery affects the revenue of Clinics. The problem in this study was high number of cataract patients who did not undergo cataract surgery with an average of 50.7% per month. This study aimed to clarify the influence Theory of Planned Behavior in generating intention to undergo cataract surgery among patients. Population under study was patients eligible for cataract surgery. Sampling was done using accidental sampling technique with a number of 67 respondents. Data collection was carried out using questionnaire and analysis was done using multiple linear regression analysis. The results indicated that variable attitude had a dominant influence on the intention to undergo cataract surgery, with value of β =0,379. The second variable was the perceived behavioral control with value of β=0,258, and the third variable was subjective norms with value of β=0,246. Therefore, it can be inferred that variable of attitudes toward behavior is factor with dominant influence on the intention to undergo cataract surgery. Finally it is expected that Mojoagung Eye Clinic to improve attitudes, perceived behavioral control and subjective norms of patients. Keywords: intention, Theory of Planned Behavior